Education Transformation in the Arctic Region of the Republic Of Sakha (Yakutia) Under the Impact of New Information Technologies in Modern Conditions - Zhirkova, Zoya S.; Kornilova, Alla G.; Amanbaeva, Lyudmila I.; Kornilov, Iurii V.; Unarova, Lyubov D. (Journal of Educational Psychology - Propositos y Representaciones, 2020)
Currently, education is considered as a multidimensional and comprehensive process of personality formation. Among other things, it contributes to the development of basic abilities such as critical thinking, problem solving ability, networking, adaptability, and initiative. Learning is continuous and widely accessible, both with regard to adaption and personalization. Nowadays, teachers are required to search for innovative technologies and techniques providing qualitative acquirement of the material and the development of key subject competencies. The objective of the study is to introduce information and communication technologies (ICT) in education. The authors use the methods of testing, questionnaire, study of documents, and reflection. The survey involves 312 full-time and part-time students of M. K. Ammosov North-Eastern Federal University (NEFU), among which 178 people represent the Arctic Region. The survey’s results are introduced in Tables 1 and 2. The results of the study are positive, with quantitative and qualitative indicators confirming the purpose of the study